Detection of Fetal Hands Abnormalities at the First Trimester Scan: A Report of Two Cases - Tsagkas, Nikolaos K.; Billis, Michail E. (Research Highlights in Disease and Health Research Vol. 5, 2023)
This report presents two cases of fetal hand abnormalities. The first is a case of unilateral fetal syndactyly discovered during a routine first trimester scan, which resulted in the early diagnosis of a severe genetic condition through invasive testing and the early termination of pregnancy. By doing so, we ensured that the woman was handled appropriately. In the second case, we describe a fetus with bilateral hand polydactyly that was combined with a cardiac defect, making extrauterine life impossible. This was once again diagnosed during the first trimester scan. In the first trimester of pregnancy, an uncomplicated abortion was performed.